Life History Traits, Elasticity Analyses, and Phenotypic Plasticity of Squaliobarbus curriculus in the Pearl River Estuary, China - Wang, Teng; Lin, Lin; Liu, Yong; Jakovlić, Ivan; Li, Chun-hou; Xiao, Ya-yuan; Wu, Peng (Frontiers in Environmental Science, 2021)
Squaliobarbus curriculus, commonly known as red-eye fish, is widely distributed in East Asia. It is one of the important aquatic germplasm resource and economic species in the Pearl River. To give suggestions for better protection and management, we investigated its life history and conducted elasticity analyses. Samples (n = 451) were collected between 2016 and 2017 from the western Pearl River estuary. There were no significant differences between the length-weight relationships of females and males (W = 0.00001SL3.121). The von Bertalanffy growth function was Lt = 553.2 [1 − e−0.111(t+1.009)]. The estimated length at 50% sexual maturity for females was 209.6 and 200.0 mm for males, both at 3 years of age. Oocyte size-frequency distribution suggested batch spawning. Fecundity ranged between 9,407 and 175,086 eggs per fish (mean = 51,040, or 143.9 eggs/g of fish weight). To better understand the ecological phenotypic plasticity of S. curriculus we conducted meta-analyses on all available life history data for this species. Our results showed that the standard lengths at ages 2 and 3 in the estuary were significantly smaller than in the upper reaches of the Pearl River basin, and there were also obvious differences in fecundity and oocyte size. For more, the standard lengths at ages 2 and 3 were correlated negatively with latitude. Elasticity analysis showed that juveniles’ (aged 1–3) survival had the largest contribution to the population growth rate, which suggests that management efforts should focus on the early life stages.